Analysis of selected international and national coach education programmes - Al-Busafi, M.; Ramadan, W. M.; Kilani, H. (Science, Movement & Health, 2012)
The purpose of this research paper was to analyze selected international and national coach education programs in order to summarize the key features of common coach education approaches around the world, sharing examples of international coach education system structures, to illustrate similarities and differences in global developments, in order to broaden understanding of global trends. Methods: Examples of international coach education system structures have been shared to illustrate similarities and differences in global developments, and to broaden understanding of global trends. In addition, the case studies discussed here involved travelling to attend different international and national coach education courses, keeping field journal notes (FJN), and gathering documents to review systems. These systems were described and critiqued, comparing the following points: accreditation structure, modes of delivery, generic/specialization systems and management. Results: The international and national cases provide further learning possibilities by identifying the strengths and challenges of other systems, critiquing them in relation to advantages and disadvantages of globalization and using outcomes to build foundation principles for the development proposal for coach education in other countries. This research also provides suggestions which help organizing international coach education programs better. Conclusion: It was concluded, that each sports organization should establish quality control of educational programmes for sport coaches according to their own financial, political and cultural situations, and they should seek to continually improve the quality of the coach education process and ensure that coaches have on-going pathways for further development.